Pelatihan Dan Pendampingan Bisnis UMKM “Kripik Tempe Rohani”: Upaya Meningkatkan Literasi Keuangan - Tatas Ridho Nugroho; Hari Setiono; Muhammad Bahril Ilmiddaviq; Nurdiana Fitri Isnaini (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
The involvement of accounting and management lecturers in the training and business support of micro, small, and medium enterprises (UMKM) and Kripik Tempe Rohani plays a crucial role in the advancement of UMKM and the local economy. This scholarly article explores the significance of initiatives aimed at enhancing financial literacy. The lecturer specialising in accounting and management delivers comprehensive training sessions on financial management, taxation, and accounting practices to micro, small, and medium enterprises (UMKM). Additionally, the lecturer offers valuable advice on the practical implementation of these principles within the context of everyday business operations. Furthermore, the instructor has the capability to acquaint UMKM (micro, small, and medium enterprises) with accounting software and provide guidance on comprehending tax responsibilities. The positive effects encompass enhanced economic well-being of micro, small, and medium enterprises (UMKMs), less business risk, adherence to tax responsibilities, sustained growth, heightened competitiveness, and facilitation of local economic progress. The provision of training and support services additionally enhances individuals' financial literacy, thereby playing a significant part in the overall improvement of society's economy.